Talking Tigers: Concepts of Representational Ethics Applied to Non-Human Characters in Writing Children’s Fiction - Mimi Thebo (Leaf Journal)
This is a paper to open discussion about the representation of animals in children’s fiction. Arguing that the destruction of animal habitats and the reduction of non-human species intersect with colonial practice, the author looks at the tradition of animal characters in children’s fiction from a practitioner’s point of view. While appreciative of the emotional experiences animal characters provide, the author asks if ethical concepts of representation might be fruitfully applied to writing animals for young readers.